Elucidating the effects of mTOR inhibitors from Malaysian natural products on tuberous sclerosis complex cell line - Zulkipli, Ninie Nadia (2022)
Mammalian target of rapamycin (mTOR) inhibitors are a highly recommended first-line therapy for tuberous sclerosis complex (TSC)-associated angiomyolipoma. Everolimus has been approved by the United States Food and Drug Administration (USFDA) for treatment of TSC-related angiomyolipoma that do not require urgent surgery. However, everolimus showed only modest efficacy for angiomyolipoma and has several other limitations. This present study aimed to identify potential mTOR inhibitor from Malaysian local sources as an alternative to everolimus in treating angiomyolipoma. The first stage of this present study involved virtual screening and docking using in silico approach to identify potential mTOR inhibitors from a local NADI database. AutoDock Vina was applied for virtually screening everolimus and more than 4000 substances (ligands) from over 360 plants species simultaneously against FKBP5 and FRB-domain of mTOR. Everolimus acted as positive control and benchmark for further selection of potential mTOR inhibitors. AutoDock 4.2.6 was later applied to identify the binding pose of each substance with the lowest docking score. The second stage of the study involved cell-based bioassays using UMB1949 cell line as TSC model to validate the in silico finding and evaluate the toxicity of the substances in vitro. The last stage of the study involved evaluation of the effects of substances on genes expression in the mTOR pathway using reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) technique. It was discovered asiaticoside and asiatic acid, two bioactive substances from Centella asiatica have lower and closer docking score to everolimus (– 11.86 kcal/mol) and have met the selection criteria as potential mTOR inhibitors. IC50 values of asiaticoside and asiatic acid were 300 μM and 60 μM, respectively. These values were higher than everolimus (29.5 μM) but they exhibited comparable antiproliferative activities in vitro. CAB39, PRKCE, RRAGC, and RPS6KA5 were upregulated by all three substances, everolimus, asiaticoside and asiatic acid. DEPTOR was commonly downregulated by all three substances. VEGFC (downregulated by asiaticoside) and IGFBP3 (downregulated by everolimus and asiatic acid) were also selected as genes of interest due to their reported roles in aiding tumour angiogenesis and apoptosis, and possible mTOR inhibition. This is the first study to look at identifying possible therapeutic potentials of asiaticoside and asiatic acid in TSC disease model that targets mTOR inhibition. These findings, in combination with our in silico findings, provide a basis for more research into the mechanisms of action, safety, and efficacy of these substances as mTOR inhibitors.